Pengaruh Penerapan E-Filing, Tingkat Pemahaman Perpajakan dan Lingkungan Wajib Pajak terhadap Kepatuhan Wajib Pajak - Eka Rohma Wati (Universitas Muhammadiyah Gresik, 2022)
The purpose of this study was to determine the effect of the implementation of e-filing, level of understanding of taxation, taxpayer environment on individual taxpayer compliance. The sample in this study is an individual taxpayer who has a NPWP registered at KPP Pratama Gresik which includes the areas of Gresik, manyar, cerme, benjeng. Sampling was done by means of random sampling (random) which includes employees, entrepreneurs, professionals. This study uses primary data. The sample used in this study was 100 respondents.The results of this study indicate that the implementation of e-filing has a significant effect on individual tax compliance, the level of understanding of taxation variables does not have a significant effect on individual taxpayer compliance, and the taxpayer environment variable has a significant effect on individual taxpayer compliance..